(untitled) (Biological Sciences - PJSIR, 2025)
During a survey of household gardens in Calabar (Nigeria) between the growing seasons 2021 and 2022, yellowing, mosaic and vein banding in the leaves, as well as severe stunting, were reported in scent leaf plants (Ocimum gratissimum family Lamiaceae). Diagnostic investigations of host range in the obtained symptomatic samples of the virus suggested a restricted host range, while ACP-ELISA results demonstrated that the isolate reacted positively with the poty virus antisera. Poty virus was further established when a pair of poty virus specific primers produced an amplicon of 700 bp from symptomatic samples. The amplicon was cloned and sequenced before the analysis of the basic local alignment search tool revealed that the cylindrical inclusion (CI) gene showed a 71.11% relationship to the Yam mosaic virus (MG711313). Phylogenetic analysis of the sequence with selected poty virus sequences from NCBI revealed it was nearest in closeness to Yam mosaic virus (MG711313) but was also in the same subgroup with Mullein poty virus (KU962959), Barleria repens mottle virus (ON854904) and PRSV (KF155416). The isolate in this investigation was tentatively determined to be a potyvirus species based on sequence identity at both the nucleic acid and protein levels, as well as phylogenetic analysis.